Long-term outcomes and recurrence-free interval after the treatment of keloids with a standardized protocol. Issue 1 (February 2021) - Maeda, T.; Funayama, E.; Yamamoto, Y.; Murao, N.; Osawa, M.; Ishikawa, K.; Hayashi, T.
Abstract: Background: Recurrence rates of keloids have generally been reported at one time point. However, the longer the duration after treatment, the greater the likelihood that such lesions will recur. In this study, we analysed the time to recurrence during long-term follow-up. Material and methods: We retrospectively reviewed recurrence-free interval in 52 patients with keloid (age 8–79 years) who had been treated between June 2006 and January 2011 using a standardised protocol developed by our group. Results: Mean duration of follow-up was 37.5 (range, 7–120) months in patients with keloid. Kaplan-Meier survival curves revealed a statistically significant difference in recurrence-free interval between ear keloids and keloids excluding ear keloids. Recurrence rate for keloids was high in the first 2 years after treatment. Conclusions: Kaplan-Meier analysis was useful for understanding the tendency of recurrence of keloids after treatment using a standardised protocol. Highlights: The Kaplan-Meier curve analysis is useful for evaluating the time to recurrence of keloids. 2 years after treatment is a critical time point when considering the risk of keloids' recurrence. Recurrence-free interval for ear keloids is significantly longer than that for other keloids.